Ultra-robust wide-range pressure sensor with fast response based on polyurethane foam doubly coated with conformal silicone rubber and CNT/TPU nanocomposites islands. (15th November 2019) - Lee, Jaehyuk; Kim, Jaehyung; Shin, Yujin; Jung, Inhwa
Abstract: Highly durable piezo-resistive pressure sensors with excellent repeatability and fast response were developed. The developed sensor have a characteristic of coated with silicone rubber, which has widened pressure measurement range and improved response time. The sensor is capable of measuring pressures lower than 100Pa and higher than 200 kPa and can measure oscillating pressure well above 50 Hz. The sensor showed high repeatability and durability and operated normally after 1000 cycles at 360 kPa applied pressure. The sensor was made by coating polyurethane foam with silicone rubber and further dip-coated with MWCNT dispersed TPU ink. The use of TPU as a binding material helped MWCNT strongly attach to the foam skeleton and reduced the interfacial electrical resistance. As a result, low hysteresis (6.4%) was achieved. By controlling amount of silicone rubber impregnated, the sensitivity can be controlled from 0.013 kPa −1 to 0.032 kPa −1 . These sensors were used for measuring both subtle pressures such as the pulse and large pressures such as the pressure beneath a heel. Additionally, wide range of pressure distributions were measured using the array sensors. The economic value of this sensor is tremendous because it can be used in a wide pressure range where high repeatability and fast response are required. Graphical abstract: Image 1 Highlights: Highly durable piezo-resistive pressure sensors with excellent repeatability and fast response were developed. The sensor made by coating PU foam with silicone rubber and capable of measuring pressures below 100Pa and above 200kPa. In addition, the use of TPU helped MWCNTs strongly attach to the skeleton and reduced the interfacial electrical resistance. It showed fast response, which can measure oscillating pressure well above 50Hz. It can measure subtle pressures such as the pulse of the human body and large pressures such as the pressure beneath a heel.